God in Contemporary Thought: The Question of Origin - A Cosmological Approach: - naffaa, rami (Arts and Social Sciences Series, 2026)
The findings of contemporary science, particularly in the field of cosmology, represent a new frontier for investigating the existence of a Creator. Consequently, this study draws upon scientific theories and positions across multiple disciplines—notably physics and optics—specifically within the context of cosmic chronology and cosmogony. It examines the implications of these findings as they pertain to the postulation of a First Cause or Creator.